2005
DOI: 10.1111/j.1075-122x.2005.21700.x
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Cryoablation of Breast Fibroadenomas with Long-Term Follow-up

Abstract: Approximately 10% of women will experience a breast fibroadenoma in their lifetime. Cryoablation is a new treatment that combines the better attributes of the current standards: surveillance and surgery. It is a minimally invasive office-based procedure that is administered without the use of general anesthesia, involving minimal patient discomfort and little to no scarring. This work aimed to establish the long-term (2-3 years) efficacy, safety, and satisfaction of the procedure, as well as the impact of cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 33 publications
(68 reference statements)
2
56
1
Order By: Relevance
“…Based on these considerations, percutaneous breast cancer ablation techniques should be carefully avoided in DCIS, representing an ideal technique for tumours below 15-16 mm in diameter. Experiences with excellent results for breast expansion of significantly greater dimensions are reported for the fibroadenomas [14,15] .The main disadvantage of in situ breast cancer ablation techniques not followed by surgical resection consists on the impossibility to assess anatomo-pathological changes, the excisional surgical specimen, the extent and completeness of ablation. Literature reported a cryotherapy experience not followed by surgical excision performed on animals [16].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations, percutaneous breast cancer ablation techniques should be carefully avoided in DCIS, representing an ideal technique for tumours below 15-16 mm in diameter. Experiences with excellent results for breast expansion of significantly greater dimensions are reported for the fibroadenomas [14,15] .The main disadvantage of in situ breast cancer ablation techniques not followed by surgical resection consists on the impossibility to assess anatomo-pathological changes, the excisional surgical specimen, the extent and completeness of ablation. Literature reported a cryotherapy experience not followed by surgical excision performed on animals [16].…”
Section: Discussionmentioning
confidence: 99%
“…For benign breast tumors cryotherapy is a preferred method, particularly in women who want to have management without an open operation [19]. Similar results are also expected with management of malignant breast tumors.…”
Section: Discussionmentioning
confidence: 56%
“…In comparison with open surgery percutaneous cryotherapy provides better patient comfort, shorter hospitalization and lower costs. In addition, as the results of a 2-3 year follow-up showed, the tendency for scar formation can be reduced by cryotherapy of fibroadenomas without a detectable volume deficit by visual examination or on palpation [19]. In the case of malignant histological findings evaluation of HER-2 and hormone receptor status on a needle biopsy sample as well as a minimally invasive sentinel lymph node resection which are usual adjuvant processes in breast saving surgery have to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the fibroadenoma patients had their palpable residual nodule excised, both revealing necrotic debris and no viable tumor in the treated volume. One year later, Kaufman et al (12) further showed the effectiveness and safety of cryoablation as a primary therapy for breast fibroadenomas. Thirty-seven treated fibroadenomas received an average follow-up period of 2.6 years, only 16% remained palpable.…”
Section: Clinical Resultsmentioning
confidence: 99%